Professionalization in Teacher Education As an Interorganizational Learning Challenge - de Boer, Heike; Fahrenwald, Claudia; Spies, Anke (Frontiers in Education, 2018)
Cultural and social changes, new administrative regulations and curricular reforms have had a significant impact on the work and professional self-image of future teachers in many European countries involved in the Bologna Process. This constellation gives rise to new challenges for established routines, practices and identities of the organizations involved in teacher education. This article deals with processes of professionalization in teacher education and presents new forms of interorganizational cooperation between schools, universities, education authorities and extracurricular agencies. Three case studies from Germany and Austria clearly demonstrate that different organizational cultures as well as different professional self-images meet in cooperative environments. The goal of the article is to analyse systematically the various interorganizational learning challenges in the field of teacher education.